A Diamond-Based Electrode for Detection of Neurochemicals in the Human Brain - Bennet, Kevin E.; Tomshine, Jonathan R.; Min, Hoon-Ki; Manciu, Felicia S.; Marsh, Michael P.; Paek, Seungleal B.; Settell, Megan L.; Nicolai, Evan N.; Blaha, Charles D.; Kouzani, Abbas Z.; Chang, Su-Youne; Lee, Kendall H. (Frontiers in Human Neuroscience, 2016)
Deep brain stimulation (DBS), a surgical technique to treat certain neurologic and psychiatric conditions, relies on pre-determined stimulation parameters in an open-loop configuration. The major advancement in DBS devices is a closed-loop system that uses neurophysiologic feedback to dynamically adjust stimulation frequency and amplitude. Stimulation-driven neurochemical release can be measured by fast-scan cyclic voltammetry (FSCV), but existing FSCV electrodes rely on carbon fiber, which degrades quickly during use and is therefore unsuitable for chronic neurochemical recording. To address this issue, we developed durable, synthetic boron-doped diamond-based electrodes capable of measuring neurochemical release in humans. Compared to carbon fiber electrodes, they were more than two orders-of-magnitude more physically-robust and demonstrated longevity in vitro without deterioration. Applied for the first time in humans, diamond electrode recordings from thalamic targets in patients (n=4) undergoing DBS for tremor produced signals consistent with adenosine release at a sensitivity comparable to carbon fiber electrodes.